(untitled) (Revista de História da UEG (REVHIST), 2023)
Far from being a phenomenon of the present time, the concern with the destruction of the biophysical environment accompanies the Capitalocene. Concerns about the environment manifested in the past, however, have specificities, and should not be confused with environmentalism and the notion of contemporary sustainability. In this way, an unfolding of the regional portrait of the picture that Pádua (2002) drew on a national scale is proposed, mapping and discussing the matrices of the Brazilian ecological tradition. In this sense, this study focuses on Paraná Provincial in order to understand how the environmental debates coming from the Central Government reverberated in Paraná lands and, also, how in the Province preservation took practical formats such as laws and decrees. To this end, official documents are taken as the main sources, above all, on the exploitation of araucaria and mate, which allow us to verify the positions and postures of the State in relation to the environment. Keywords: Environmental History. Brazil Impire. Province of Paraná. Environmental Critique.